2023
DOI: 10.7150/thno.80555
|View full text |Cite
|
Sign up to set email alerts
|

Platelets promote CRC by activating the C5a/C5aR1 axis via PSGL-1/JNK/STAT1 signaling in tumor-associated macrophages

Abstract: Rationale: Platelets can influence the progression and prognosis of colorectal cancer (CRC) through multiple mechanisms, including crosstalk with tumor-associated macrophages (TAMs). However, the mechanisms underlying the crosstalk between platelets and TAMs remain unclear. The present study aimed to investigate the role of intratumoral platelets in regulating the function of TAMs and to identify the underlying mechanisms. Methods: The interaction of platelets with macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…It has also been shown that intratumoral platelets promoted growth and progression of colorectal cancer leading to JNK/STAT1 signaling activation, which further promoted C5 transcription and activated the C5a/C5aR1 axis in tumor-associated macrophages (TAMs). Shifting TAMs toward M2 polarization and impairing the phagocytosis of TAMs was followed by the increased mRNA levels of Arg1 and IL-10 in sorted TAMs [ 64 , 65 ] ( Fig. 2 ).…”
Section: Platelets and Myeloid Cellsmentioning
confidence: 99%
“…It has also been shown that intratumoral platelets promoted growth and progression of colorectal cancer leading to JNK/STAT1 signaling activation, which further promoted C5 transcription and activated the C5a/C5aR1 axis in tumor-associated macrophages (TAMs). Shifting TAMs toward M2 polarization and impairing the phagocytosis of TAMs was followed by the increased mRNA levels of Arg1 and IL-10 in sorted TAMs [ 64 , 65 ] ( Fig. 2 ).…”
Section: Platelets and Myeloid Cellsmentioning
confidence: 99%
“…Xueqin Li et al have found elevated TEPs can promote the growth and metastasis of CRC by binding CD62P to PSGL-1 expressed on tumor macrophages (TAMs), enhance the C5 transcription in TAMs and activate the C5a/C5aR1 axis via the JNK/STAT1 pathway. The study explored the mechanism by which the interaction between platelets and TAMs can aggravate the development of CRC and proposed a potential therapeutic strategy for CRC patients [ 125 ]. While previous research suggests that platelets can influence the course and outcome of CRC through interactions with TAMs, the precise mechanisms remain unclear.…”
Section: Tumor-associated Platelets In Crcmentioning
confidence: 99%
“…This correlation can be explained mostly by elevation of prothrombotic factor expression by either cancer cells or cells forming the tumor microenvironment [2,3]. These mechanisms are self-reinforcing processes because platelets present the ability to promote progression of the cancer [4,5]. Among molecular mechanisms of tumor cell-induced platelet aggregation (TCIPA), scientists described production of tissue factor (TF) by cancer cells [6], production and regulation of thrombopoietin (TPO) [7], and granulocyte colony stimulating factor [8].…”
Section: Introductionmentioning
confidence: 99%